Fracture toughness investigations of Al6061-Graphite particulate composite using compact specimens - Saleemsab Doddamani; Mohamed Kaleemulla (Fracture and Structural Integrity)
The objective of this research work is to study the fracture behavior of Al6061 with graphite particulate composite produced by the stir casting technique. For the study different composition of the particulate metal matrix composite used is Al6061 with 3, 6, 9, & 12% of graphite particles. Compact Tension (CT) specimens were utilized to determine fracture toughness for different compositions of Al6061-graphite particulate metal matrix composite. Specimens with different composition will be prepared for different crack length to width (a/w) ratios according to the ASTM E-399 standard testing procedure. The maximum fracture toughness was found for Al6061-9%Gr for a/w =0.45 and the value is 16.74 MPa ?m.